Interaction of punches on orthotropic half-space - Dmitry A. Pozharskiy; Tatiana G. Yurushkina (Advanced Engineering Research, 2016)
An integral equation of the three-dimensional contact problem for an orthotropic half-space (9 independent elastic parameters in Hooke’s law) is obtained where its kernel does not include integrals, but it depends on the solution of a characteristic binary cubic. The interaction between two identical symmetrically embedded punches is considered for the case of the elliptic paraboloids. Galanov’s method of nonlinear boundary integral equations is used for solving the problem with an unknown contact domain that makes it possible to determine simultaneously the contact domain and the contact pressure. The exact solution to one elliptical punch is used for debugging the computer program. Contact pressures, contact zones and pressing forces are calculated for various orthotropic materials at the specified settlement, base forms of the punches, and relative distances between the punches. The orthotropic body model is applicable for describing lots of materials which are in-demand in the machinery and industry: sulfur, Rochelle salt, wolframite, barite, and various wood species.